2016
DOI: 10.5751/es-08933-210433
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance for cougars diminished by high perception of risk

Abstract: ABSTRACT. In North America, both human and cougar populations are expanding and increasingly sharing the same space, including modified landscapes viewed by people as their "backyard." Low tolerance for cougars in modified landscapes has been identified as a key factor that could restrict continued cougar range expansion in North America, or even reverse some of the gains made by cougar populations in recent decades. To better understand factors influencing tolerance and identify opportunities to improve conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Despite some examples of successful coexistence, support for conserving carnivores is not uniform and can vary between groups of people, including rural land owners and urban residents, particularly when rural people might directly interact with these animals (Kellert et al, 1996;Bjerke and Kaltenborn, 1999;Ericsson et al, 2004;Karlsson and Sjöström, 2007;Hughes and Nielsen, 2018). In a rural context, tolerance for large carnivores may be contingent on reducing the safety risks or economic impacts on human livelihoods these species can cause (Riley and Decker, 2000;Ericsson et al, 2008;Knopff et al, 2016;Hughes and Nielsen, 2018). Further, rural communities and agricultural areas typically bear the costs of living with carnivores (Newsome et al, 2015;Morehouse and Boyce, 2017;Hughes and Nielsen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some examples of successful coexistence, support for conserving carnivores is not uniform and can vary between groups of people, including rural land owners and urban residents, particularly when rural people might directly interact with these animals (Kellert et al, 1996;Bjerke and Kaltenborn, 1999;Ericsson et al, 2004;Karlsson and Sjöström, 2007;Hughes and Nielsen, 2018). In a rural context, tolerance for large carnivores may be contingent on reducing the safety risks or economic impacts on human livelihoods these species can cause (Riley and Decker, 2000;Ericsson et al, 2008;Knopff et al, 2016;Hughes and Nielsen, 2018). Further, rural communities and agricultural areas typically bear the costs of living with carnivores (Newsome et al, 2015;Morehouse and Boyce, 2017;Hughes and Nielsen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We could not verify this claim since other people feared retaliation from hunters. Also, hunters were substantially less tolerant than non-hunters (Knopff et al 2016), and indicated they will do it again if needed, and if they have problems with bears, they cannot count with any authority to help them, and prefer to "eliminate the problem". This was also discussed by Dickman (2010), who indicated that the response to conflict often appears disproportionate and even a small level of wildlife damage can still elicit harsh responses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduced number of sightings and damage to crops, the perception of the people towards the Andean bear remains negative. The substantial overestimation of risk associated with carnivores, including bears, could be the result of a cognitive illusion, which occurs when rare events are so memorable and easily recalled that individuals overestimate their frequency (Knopff et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Human-large carnivore conflict is the major barrier to the conservation of these species and attacks on humans represent the most extreme form of such conflict. It is well-recognized that human acceptance of large carnivores plays a crucial role in the fate of these species (Ripple et al, 2014) and acceptance highly depends on the real or perceived risk that these species pose to human safety (Decker et al, 2002;Knopff et al, 2016). Thus, Abbreviations: SM, Social Media; NTS, Number of Total Shares.…”
Section: Introductionmentioning
confidence: 99%